Managerial Stock Ownership and the Maturity Structure of Corporate Debt - DATTA, SUDIP; ISKANDAR‐DATTA, MAI; RAMAN, KARTIK (Journal of Finance, 2005)
ABSTRACT This study documents that managerial stock ownership plays an important role in determining corporate debt maturity. Controlling for previously identified determinants of debt maturity and modeling leverage and debt maturity as jointly endogenous, we document a significant and robust inverse relation between managerial stock ownership and corporate debt maturity. We also show that managerial stock ownership influences the relation between credit quality and debt maturity and between growth opportunities and debt maturity.